STUDENT’S PERCEPTION IN READING INDONESIA FOLKLORES ON THEIR ENGLISH TEXTBOOK - Heni Novita Sari (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
This study investigates tenth grade students’ perceptions on English textbooks which contain Indonesian Folklores as its reading materials. This study focuses on finding out students’ original perspectives on Indonesian Folklores in English textbook which may have three possibilities; either positive, neutral, or negative views. To get the answer, this study applied both close- ended and open-ended questionnaires as instruments of the research within mix method research’s design (quantitative and qualitative). The respondents were 60 tenth grade students of Senior High Schools in Jabodetabek. The results of the close-ended questionnaire showed that 1) reading Indonesian Folklores is interesting, fun, and motivating with the mean of 43, and 2) Reading Indonesian Folklores emerge cultural awareness with the mean of 47 responses in positive agreement with Indonesian Folklores in English Textbook. It was followed by one item in the open-ended questionnaire to get more accurate perceptions about whether English textbooks containing folklore is useful in increasing interest in learning English reading as well as protecting cultural preservation. The findings reveal that students have positive perceptions of Indonesia folklores in English Textbook, which makes them motivated and builds their cultural awareness.